Multicenter lupus register from Argentina, the RELESSAR database: Influence of ethnicity on disease phenotype. (April 2022) - García, Mercedes A; Alba, Paula; del Campo-Perez, Victor; Roverano, Susana; Quintana, Rosana M; Alvarez, Analia P; Graf, Cesar E; Pisoni, Cecilia; Spindler, Alberto; Gomez, Catalina; Figueredo, Heber M; Papasidero, Silvia; et al.
Objective: The objective is to describe the main characteristics of patients with systemic lupus erythematosus (SLE) in Argentina and to examine the influence of ethnicity on the expression of the disease. Patients and methods: RELESSAR is a multicentre register carried out by 106 researchers from 67 rheumatologic Argentine centres. It is a cross-sectional study of SLE (1982/1997 ACR) patients. RELESSAR electronic database includes demographic, cumulative SLE manifestations, SELENA-SLEDAI, SLICC-SDI, Katz's severity and Charlson's comorbidity indexes and treatment patterns. Results: We included 1, 610 patients, 91.7% were female with a median age at diagnosis of 28.1 ± 12.8; 96.2% met ≥4 ACR 1982/97 criteria. Frequent manifestations were arthritis (83.5%), malar rash (79.5%), photosensitivity (75.3%), haematological (63.8%) and renal disease (47.4%), antinuclear antibodies (96%), anti-dsDNA (66.5%) and anti-Smith antibodies (29%). The mean Selena-SLEDAI score at last visit was 3.18 (SD 4.3) and mean SDI was 1 (SD 1.3). The accumulated treatments most frequently used were antimalarials (90.4%), corticosteroids (90%), azathioprine (31.8%), intravenous cyclophosphamide (30.2%), mycophenolate mofetil or mycophenolic acid (24.5%), methotrexate (19.3%), belimumab 5.3% and rituximab 5.1%. Refractory lupus was diagnosed in 9.3% of the cases. The main causes of death were lupus activity (25.0%), activity and concomitant infections (25.0%), infections (18.2%), vascular disease (13.6%) and cancer (4.5%). Mortality was associated with higher SLEDAI, Katz, damage indexes and comorbidities. Of the 1610 patients included, 44.6% were Caucasian, 44.5% Mestizo, 8.1% Amerindian and 1.2% Afro-Latin American. Mestizo patients had higher male representation, low socioeconomic status, more inadequate medical coverage, fewer formal years of education and shorter disease duration. Polyadenopathies and Raynaud's phenomenon were more frequent in Caucasians. In the logistic regression analysis higher damage index (OR 1.28, CI 95% 1.02–1.61, p = 0.03) remained associated to mestizo ethnicity. Conclusions: This study represents the largest number of adult patients with SLE studied in Argentina. Caucasian patients were differentiated by having Raynaud's phenomenon and polyadenopathy more frequently, while patients of Mestizo origin had higher damage indexes.